Trans-orbital penetrating head injury (TOPHI): Short series of two cases with review of literature - Satyarthee, Guru Dutta; Dawar, Pankaj; Borkar, Sachin A.; Sharma, Bhawani Shankar (Indian Journal of Neurotrauma, 2014)
Penetrating head injury of brain is uncommon form of external compound injury account for nearly 0.4% of head injuries. Transorbital penetrating head injuries (TOPHI) are still rarer Authors report two cases, first reported immediately caused by ceramic stone while second after lapse of three months following injury due to wooden twig, both underwent surgery with removal of foreign body with good outcome. Proper clinical history, examination and CT scan to evaluate trajectory and CT angiography to assess vascular anatomy are prerequisite for proper planning and management. Management of such cases and pertinent literature is reviewed.
Keywords: Penetrating injury; Transorbital injury; Skull base; Cranio-cerebral injury